Preferensi Objek Zakat Fase Klasik dalam Aklimatisasi Hukum dan Problematika Fikih Kontemporer - Maulana, Nora (Syarah: Jurnal Hukum Islam dan Ekonomi, 2023)
Academic discourse regarding classical zakat objects that are mapped with modern problems has not been investigated much, so it needs to be underlined that the lack of available literature is one of the causes of low public literacy so that zakat assets are not optimally realized. These conditions make this research more feasible and important to study in Islamic philanthropic work. This study is also interesting to study because it discusses the classical phase of zakat objects which are interconnected with the conditions of society in the modern era so that they are very useful in broadening the scope and literacy of society regarding zakat objects in a comprehensive manner. This study uses a descriptive qualitative method with a Systematic Literature Review (SLR) approach. The research data sources were obtained from books, journals, articles, and scientific sources related to the topic of study. Data analysis was carried out by adopting Miles and Huberman's theory through reduction, presentation, and conclusion. The research findings show that the development of classical zakat objects in the contemporary era occurs in agricultural, livestock and fisheries zakat. In agricultural zakat, it is obligatory to pay zakat on productive plants. Meanwhile, zakat on livestock and fisheries includes zakat on poultry livestock, both broiler and laying eggs, zakat on honey livestock, zakat on land fisheries, and zakat on marine products.